IMPROVING STUDENTS’ READING COMPREHENSION THROUGH LISTEN-READ-DISCUSS (LRD) STRATEGY AT ELEVEN GRADE OF MAN DHARMASRAYA - Geofani Amelia; Suparmi; Rahma Dania (Cahaya Ilmu Bangsa Institute, 2023)
The purpose of this research is to find out the significant differences in improving students' reading comprehension by using the Listen-Read-Discuss (LRD) strategy. This research was conducted on class XI IPK students at MAN Dharmasraya. In this study, the researcher only took one class as a sample. The sample consisted of 28 students of class XI IPK and was selected using a saturated sample technique. The material taught by research uses biography texts. This study used a quantitative method with a pre-experimental approach. Research used data collection techniques Pre-test, treatment, and post-test. The data collection instrument was a written test in the form of 10 multiple choices and 5 essays with total of 15 questions. The pre-experimental group was given pre-test and post-test. The final average value obtained from the experimental group was analyzed using the T-test formula with a significant level of α = 0.05. The results of the research conducted show that there is a significant effect of using the Listen-Read-Discuss (LRD) strategy in students' reading lessons. The results of research conducted by researcher indicate that there is a significant influence by using the Listen-Read-Discuss (LRD) strategy in students' reading lessons. From the results of the data, obtained the average score of the pre-test (1798) and post-test (2313). t-observe (3.315) and t-table (1.705). It supported by the t-test value that was higher than t-table value (3.35>1.705). Therefore, the alternative hypothesis shows that Ho is rejected and Ha is accepted. This means that there is a significant effect of using the Listen-Read-Discuss (LRD) strategy in improving reading comprehension in class XI IPK MAN Dharmasraya.